Seed germination of pitaya (Hylocereus spp.) as affected by seed extraction method, storage, germination conditions, germination assessment approach and water potential. Issue 3 (4th May 2019) - Zerpa-Catanho, Dessireé; Hernández-Pridybailo, Andrés; Madrigal-Ortiz, Viviana; Zúñiga-Centeno, Adonay; Porras-Martínez, Carolina; Jiménez, Víctor M.; Barboza-Barquero, Luis
ABSTRACT: To breed and preserve pitaya ( Hylocereus spp.) genetic resources, reliable information on seed storage and germination conditions is needed. Therefore, this study was undertaken to evaluate the effects of the following factors on germination of pitaya seeds: seed extraction method (manual vs. enzymatic seed extraction), storage time and conditions (up to 12 months at room temperature and in a cold storage chamber), germination conditions [temperature (15, 20, 25 and 30ºC) and light (blue, red and darkness)], germination assessment method (conventional vs. automated with digital image analysis), harvesting season (2014 and 2015), and water potential (−0.5, −1.0 and −2.0 MPa induced by polyethylene glycol 6000 or NaCl). Results showed that freshly extracted seeds germinated close to 100% within one week. Enzymatic seed extraction increased germination speed. Room temperature-stored seeds lost viability compared to cold-stored seeds, whose germination did not change across 12 months of storage. When seeds were germinated at 15°C and in darkness, germination rate and speed decreased. Conventional and image analysis approaches showed a high coefficient of determination when measuring seed germination and allowed to calculate additional parameters, such as maximum germination (gMAX) and time to achieve 50% germination (T50). Water potential of −0.5 MPa negatively affected seed vigor but not gMAX; germination was inhibited below −1.0 MPa. Hylocereus seeds were more affected by polyethylene glycol 6000 than by NaCl at the same water potential.